2003
DOI: 10.1023/a:1023539104747
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two consortia, isolated by selective enrichment from a soil sample of a nitroaromatic-contaminated site, degraded 2,4-DNT as their sole nitrogen source without accumulating one or more detectable intermediates. Though originating from the same sample, the optimised consortia had no common members, indicating that selective enrichment resulted in different end points. Consortium 1 and consortium 2 contained four and six bacterial species respectively, but both had two members that were able to collectively degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Several microbial strains able to use DNT as the sole carbon (17,18) or nitrogen (19,20) source were reported. DNT can serve as a potential nitrogen source through the release of either nitrite or ammonium during oxidative or reductive biotransformation, respectively (16).…”
mentioning
confidence: 99%
“…Several microbial strains able to use DNT as the sole carbon (17,18) or nitrogen (19,20) source were reported. DNT can serve as a potential nitrogen source through the release of either nitrite or ammonium during oxidative or reductive biotransformation, respectively (16).…”
mentioning
confidence: 99%
“…The diverse metabolic capabilities have supported the Variovorax paradoxus to degrade a wide range of natural and xenobiotic compounds [34]. For instance, Snellinx et al [42] reported that the Variovorax paradoxus strain VM685 is capable of degrading 2,4-dinitrotoluene (2,4-DNT) and can coexist with other 2,4-DNT-degrading strain Pseudomonas sp. VM908.…”
Section: Discussionmentioning
confidence: 99%
“…While Pseudomonas sp. have been previously reported as members of DNT-degrading consortia [3,4,24,36], several Burkholderia species have been shown to be capable of degrading DNT on their own and also as part of a consortia [4,13,37,38]. In fact, Burkholderia were the first isolated microorganisms capable of DNT degradation [39].…”
Section: Bacterial Community Diversitymentioning
confidence: 99%